2014
DOI: 10.1158/2159-8290.cd-14-0250
|View full text |Cite
|
Sign up to set email alerts
|

Serine Catabolism Regulates Mitochondrial Redox Control during Hypoxia

Abstract: The de novo synthesis of the non-essential amino acid serine is often upregulated in cancer. In this study we demonstrate that the serine catabolic enzyme, mitochondrial serine hydroxymethyltransferase (SHMT2) is induced when Myc-transformed cells are subjected to hypoxia. In mitochondria, SHMT2 can initiate the degradation of serine to CO2 and NH4+ resulting in net production of NADPH from NADP+. Knockdown of SHMT2 in Myc-dependent cells reduced cellular NADPH/NADP+ ratio, increased cellular reactive oxygen s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
356
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(368 citation statements)
references
References 47 publications
12
356
0
Order By: Relevance
“…However, we could not rescue the effects of MTH FD2 suppression in AML cell lines with the addition of up to 10 mM formate concentrations, a similar observation to that of Nilsson et al (2014). More recently, several publications supported the role of mitochondrial one-carbon metabolism in redox homeostasis and NAD PH production Ye et al, 2014). Fan et al (2014) demonstrated a decrease in the NAD PH/ NADP + ratio with MTH FD2 knockdown in HEK293T cells, and Ye et al (2014) demonstrated a decrease in the NAD PH/ NADP + ratio with SHMT2 knockdown only in hypoxic conditions in neuroblastoma cells Ye et al, 2014).…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…However, we could not rescue the effects of MTH FD2 suppression in AML cell lines with the addition of up to 10 mM formate concentrations, a similar observation to that of Nilsson et al (2014). More recently, several publications supported the role of mitochondrial one-carbon metabolism in redox homeostasis and NAD PH production Ye et al, 2014). Fan et al (2014) demonstrated a decrease in the NAD PH/ NADP + ratio with MTH FD2 knockdown in HEK293T cells, and Ye et al (2014) demonstrated a decrease in the NAD PH/ NADP + ratio with SHMT2 knockdown only in hypoxic conditions in neuroblastoma cells Ye et al, 2014).…”
Section: Discussionsupporting
confidence: 49%
“…More recently, several publications supported the role of mitochondrial one-carbon metabolism in redox homeostasis and NAD PH production Ye et al, 2014). Fan et al (2014) demonstrated a decrease in the NAD PH/ NADP + ratio with MTH FD2 knockdown in HEK293T cells, and Ye et al (2014) demonstrated a decrease in the NAD PH/ NADP + ratio with SHMT2 knockdown only in hypoxic conditions in neuroblastoma cells Ye et al, 2014). Given that MTH FD2 is an NAD + dependent enzyme, we focused on measuring NAD + /NADH ratio in AML cells after MTH FD2 suppression and did not find a consistent difference in this ratio in the AML cell line setting (unpublished data), whereas samples with ssGSEA z-scores ≤−1 were labeled as significantly low enriched in the signature and highlighted blue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De novo serine synthesis and the folate pathway are another major source of NADPH for cancer cells Lewis et al 2014;Ye et al 2014). De novo serine synthesis can be limiting for flux through the folate pathway, and reduced serine hydroxymethyltransferase expression reduces the cellular NADPH/NADP þ ratio while increasing ROS levels and cell death .…”
Section: Cancer Cells Undergo Metabolic Changes To Manage Rosmentioning
confidence: 99%
“…It was reported recently that, upon serine starvation, p53 activates p21 to promote GSH production to combat ROS [25,26]. Additionally, p73, ATF4, G9A, HIF1 and PKCζ were also reported to regulate serine biosynthesis and metabolism [27][28][29][30][31]. However, compared to the profound understanding of glycolysis and glutaminolysis in cancer cells, we are only beginning to appreciate the critical impact of serine synthesis pathway (SSP) on cancer progression.…”
Section: Introductionmentioning
confidence: 99%